Convergence of professional and amateur coverage of Eurovision Song Contest - Petrović, Bojan (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
In this paper, the author is attempting to examine the relationship between professionals and amateurs in the world of Eurovision Song Contest reporting, through the prism of the concept of cultural convergence (Jenkins, 2006.). The sample survey is made out of 17 respondents from Serbia, Croatia, Montenegro, and Bosnia and Herzegovina, ten of which are Eurovision fans who create content in their respective mother tongue and English language, five journalists, and two Eurovision commentators from RTS and HRT. The results of this research paper show that the professional media workers recognise the significance of the fan work, and that that same work is useful in their performance, while the fans describe the reporting of the mainstream media as sensationalistic, without delving into the topic, and oftentimes prone to mistakes. The fans, however, understand this type of work, and offer help with the reporting, so that the audience could have a chance to learn the most accurate information. When talking about the collaboration between fans and professionals, it is usually described as positive, and journalists do not see Eurovision fans as competition, rather as a good source of information.
Keywords: convergence culture, Eurovision Song Contest, amateur, professional, fans, coverage